PENENTUAN HARGA OPSI DENGAN MODEL BLACK-SCHOLES MENGGUNAKAN METODE BEDA HINGGA CENTER TIME CENTER SPACE (CTCS) - Welgi Okta Irawan (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2017)
Stock options is defined as a contract between two parties or two person. The first parties is a buyer the contract has a right to buy or sell some stocks to the second parties. The contract contains price of selling and buying and a certain period of time when the transaction will be done. To generate a profit, investor have to calculate the fear price from the options how the options price can be bought or sold. A model of Black-Scholes is one of modelscan be used for calculating the option price. The model is partial differential equation form. One of methodsto find a solution of the model is a finite difference of Centre Time Centre Space (CTCS). This research aims to establish the option pricing formula with Black-Scholes Models with the solution using the CTCS finite difference method.After that, it is applied to determine the option price of Apple(AAPL) stocks from the American stock exchange (NASDAQ).The results is obtained bought optionprice and sold option price at 28 July 2017 are $5.2558 and $ 0.9734. The price of bought option in the market is $5.67 (>$5.2558), so investor should to sell bought option. Whereas the price of sold option in the market is $1.32 (>$0.9734), so investor should to sell sold option.